2020
DOI: 10.1038/s41598-020-60996-2
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of PPARD and PPARG Polymorphisms on Glioma Risk and Prognosis

Abstract: Recent studies showed that peroxisome proliferator-activated receptors (PPARs) had effects on the progression of multiple tumors, but the role of PPARD and PPARG in glioma remains poorly understand. We conducted a case-control study to investigate the association of polymorphisms in PPARD and PPARG with glioma risk and prognosis in the chinese Han population. Seven polymorphisms (PPARD: rs2016520, rs67056409, rs1053049 and rs2206030; PPARG: rs2920503, rs4073770 and rs1151988) were genotyped using the Agena Mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…The outcomes revealed that the high PPARG expression group had a higher level of immune checkpoint expression. These findings support PPARG as an additional biomarker for prognosis after immunotherapy and an additional target to facilitate corresponding immunotherapy ( Ding et al, 2020 ; Ma et al, 2021 ). However, in-depth studies are required to establish further facts.…”
Section: Discussionsupporting
confidence: 68%
“…The outcomes revealed that the high PPARG expression group had a higher level of immune checkpoint expression. These findings support PPARG as an additional biomarker for prognosis after immunotherapy and an additional target to facilitate corresponding immunotherapy ( Ding et al, 2020 ; Ma et al, 2021 ). However, in-depth studies are required to establish further facts.…”
Section: Discussionsupporting
confidence: 68%
“…Studies have shown that PPARG may increase the chemical sensitivity of pharyngeal squamous cell carcinoma [ 37 , 38 ]. Studies have also shown that prognosis in the Chinese Han population is related to PPARG gene polymorphism [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that combinatorial activation of retinoic acid receptor, PRAR-α and PPAR-β/δ may be promising therapeutic approach for RA-resistant neuroblastoma patients. Ding et al ( 2020 ) demonstrated the impact of PPAR-β/δ and PPAR-γ polymorphism on glioma risk and prognosis in the Chinese Han population.…”
Section: Ppar-β/δ In Brain Tumors (Neuroblastomas and Gliomas)mentioning
confidence: 99%